2011
DOI: 10.1007/s12134-011-0224-2
|View full text |Cite
|
Sign up to set email alerts
|

Cities, Migrant Incorporation, and Ethnicity: A Network Perspective on Boundary Work

Abstract: AuthorJanine Dahinden is professor of Transnational Studies at the University of Neuchâtel. Her research interests cover topics regarding mobility, migration, ethnicity, transnationalism, social networks, gender and culture. Her research is transdisciplinary and combines qualitative and quantitative methods (see also www.unine.ch/janine.dahinden). AbstractIn this article, I am interested in the different types of boundaries emerging in a city that is characterized by a highly diverse population. The analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 30 publications
0
25
0
2
Order By: Relevance
“…It has uncovered processes that are similar to those generally associated with highly skilled migrants who navigate a globalised world and economy. Many studies focusing on "mobility" concentrate on economically and socially advantaged groups: they show how, through their cross-border movements, they become some kind of cosmopolitan elite (see for instance Fournier 2008;Ong 2003;Weiss 2005;Dahinden 2009aDahinden , 2013Bilecen and Van Mol 2017). These scholars show how highly skilled and/or economically privileged people may build on their assets to develop and benefit from highly mobile lifestyles.…”
Section: Challenging Taken-for-granted Distinctions Between Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has uncovered processes that are similar to those generally associated with highly skilled migrants who navigate a globalised world and economy. Many studies focusing on "mobility" concentrate on economically and socially advantaged groups: they show how, through their cross-border movements, they become some kind of cosmopolitan elite (see for instance Fournier 2008;Ong 2003;Weiss 2005;Dahinden 2009aDahinden , 2013Bilecen and Van Mol 2017). These scholars show how highly skilled and/or economically privileged people may build on their assets to develop and benefit from highly mobile lifestyles.…”
Section: Challenging Taken-for-granted Distinctions Between Migrationmentioning
confidence: 99%
“…Second, and relatedly, this study has shown that migrants' transnational social networks are not exclusively characterised by relationships or ties with people from the same national or ethnic background, contrary to what some scholars have implicitly assumed. While earlier studies on migrant's social networks have focused on their relationships with people with a "shared community origin" (Massey et al 1993), some scholars have started to apply what Dahinden (2013) has called a "post-ethnic approach", which attempts to examine all types of connections as they emerge from the empirical data. For example, the literature on cross-border circulation practiced by suitcase traders or those who act as intermediaries for them (Schmoll and Semi 2013;Schmoll 2005;Peraldi 2001), cabaret dancers (Dahinden 2009b(Dahinden , 2010 and mobile doctors (Tarrius et al 2013) has shed light on alternative forms of transnationality based on cosmopolitan ties.…”
Section: Differentiated Forms Of Transnationalitymentioning
confidence: 99%
“…The "global city" is a multicultural metropolis with individuals of diverse ethnic background with continuous connections around the world (Gow, 2005). Cities live up to this reputation because they exhibit features of ethnic enclaves, which, in some case, are spatially delineated (Dahinden, 2013). The ethnic plurality in cities exemplifies Vertovec's (2007) "super-diversity" notion-the interaction between elements in the context of a rising number of migrants from manifold places of origin who are demographically and economically distinguished.…”
Section: General Context and Hypothesesmentioning
confidence: 99%
“…Some authors argue that highly skilled migrants face less discrimination and higher levels of integration in general. They contend that, even when highly educated migrants know little about the host and show low anchorage or local establishment, it would be inappropriate to consider them nonintegrated unless they become part of a "visible" minority, clearly defined and therefore potential target for discrimination (Dahinden, 2013;Leinonen, 2011).…”
Section: Social Integration Of Immigrants In Times Of Crisismentioning
confidence: 99%